Efektivitas Penggunaan Media Blooket terhadap Kemampuan Literasi Membaca Teks Biografi Siswa Kelas X - Susanti, Fera; Quthny, Abu Yazid Adnan; Susetya, Hemas Haryas Harja (GERAM, 2025)
This study was designed to analyze the effectiveness of using the Blooket media to improve the reading literacy skills of students in grade X on the topic of biographical texts at SMA Negeri 1 Maron. Literasi membaca dalam kajian ini mencakup kemampuan untuk memahami dan menganalisis isi teks biografi. The study is based on the low reading literacy level of students and the need for innovative educational media that is engaging and relevant to the needs of today's students. The research method used in this study is quantitative with a quasi-experimental design. The research sample consists of 36 students from class XA as the experimental group and 34 students from class XB as the control group. The instruments used were student satisfaction questionnaires and tests (pre-test and post-test). Data dianalisis dengan bantuan software SPSS 22, meliputi uji validitas, reliabilitas, normalitas, homogenitas, independent sample t-test, dan N-gain score. The results of the study showed that the questionnaire was valid and reliable (r calculated ≥ 0.632 and α = 0.761). Independent sample t-test analysis revealed significant differences between the posttest results of the experimental and control groups (sig. 0.000 < 0.05). The average N-gain score for the experimental group was 64.8%, which is considered moderately effective. Sebanyak 94% siswa merespons positif terhadap penggunaan media Blooket. Blooket media has proven to be effective in increasing reading literacy and motivating students through enjoyable learning media.